2021
DOI: 10.2147/ca.s290119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Audit on Current Practice of Anesthesia Machine Check and Equipment Preparedness Before Use in Debre Berhan Comprehensive Specialized Hospital, North Shewa, Ethiopia, 2020

Abstract: Background: Assessing the quality assurance of providing work-ready anesthesia equipment in operating rooms is so vital. Most of the anesthesia-related adverse events are preventable by the identification and correction of anesthesia machine errors and equipment preparation in the pre-induction period. This paper aimed to keep a high-quality environment for workers and patients in the surgical operating theater. Materials and Methods: Data were collected after ethical clearance obtained from the institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This result showed that anesthesia machine check and equipment preparation is more or less similar to the clinical audit done by Samuel Debasu and his colleagues at Debre Birhan referral hospital but, the Debre Birhan study was conducted among 61 machine checks. Whereas, our study was conducted among 202 checking events [ 20 ]. However, this study is under practiced when compared with most standards [ 18 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result showed that anesthesia machine check and equipment preparation is more or less similar to the clinical audit done by Samuel Debasu and his colleagues at Debre Birhan referral hospital but, the Debre Birhan study was conducted among 61 machine checks. Whereas, our study was conducted among 202 checking events [ 20 ]. However, this study is under practiced when compared with most standards [ 18 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, according to the national audit project (NAP4) report the most contributing factors for poor outcomes regarding airway management were deficiencies in judgment and inadequate equipment preparedness. As evidence recommends, machine checks and airway equipment be performed on daily basis [ 10 , 14 , [18] , [19] , [20] , [21] ]. Furthermore, The properly labeled equipment container provides the right equipment, in the right amount, in the right place, at the right time [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%